Production-ready applied deep learning : learn how to construct and deploy complex models in PyTorch and TensorFflow deep-learning frameworks /: learn how to construct and deploy complex models in PyTorch and TensorFflow deep-learning frameworks. (2022) - Palczewski, Tomasz; Lee, Jaejun; Mookiah, Lenin
No abstract available